Methodology of Complex Analysis of Return on Sales - Mackevičius, Jonas; Molienė, Ona; Poškaitė, Dalia (Ekonomika, 2008)
The effectiveness of the activity of an enterprise is assessed using the profitability ratios. In practice, the effectiveness of enterprises is measured by various profitability ratios which have different methods of calculations, different definitions and names. This makes some difficulties in calculations and analysis of profitability ratios.An investigation carried out by the authors (October 2007) shows that only 35 enterprises, or 47% of all those taken into account, count profitability ratios, while 38 enterprises, or 52.1%, don’t count these ratios and don’t make their analysis. The results of the investigation allow to conclude that it is necessary to analyze profitability ratios and to disclose the reserves of the effectiveness of enterprises.Profitability ratios should be defined as return on gross profit, on sales and on activity costs. Profitability ratios have a strong connection with sales, assets and owner’s equity. For that reason, the ratios should be c1assified into groups of return on sales. return on assets and return on owner’s equity. This way of classification of profitability ratios would help the users of information not only to understand better the methodology of calculation, but also to make more correct decisions. Breaking up the profitability ratios into groups of return on sales, return on assets and return on capital is very important for different users interested in different information significant for them. Information users seem to be more interested in return on sales.